Packaging materials and containers

By using the polyester urea-type adhesive layer and basic aqueous solution separation technology in the packaging material, the problems of bonding, boiling and heating resistance and second sub-layer recycling in the prior art are solved, and efficient packaging material performance and recycling effect are achieved.

JP7665961B2Active Publication Date: 2025-04-22TOYO INK MFG CO LTD +1
View PDF 7 Cites 0 Cited by

Patent Information

Application Number
JP2020193765
Authority / Receiving Office
JP · JP
Patent Type
Patents
Current Assignee / Owner
Priority Date
2019-11-25
Filing Date
2020-11-20
Publication Date
2025-04-22
Estimated Expiration
2040-11-20

Smart Images

  • Figure 0007665961000001
    Figure 0007665961000001
  • Figure 0007665961000002
    Figure 0007665961000002
  • Figure 0007665961000003
    Figure 0007665961000003
Patent Text Reader

Abstract

To provide a packaging material that has excellent adhesive strength and boil-retort resistance, and is excellent in the separation or desorption of a sealant base material from the packaging material, and a package formed from the packaging material.SOLUTION: A packaging material has a structure in which at least a first base material, a printed layer, a polyurethane adhesive layer for the detachment of a second base material, and the second base material are laminated from the outer layer side in the stated order, the polyurethane adhesive layer being provided in contact with the second base material. A package is formed from the packaging material.SELECTED DRAWING: None
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to a packaging material suitable for the recyclability of plastic substrates, and a packaging container formed from the packaging material. [Background technology]

[0002] In recent years, packaging made from plastic film, plastic bottles, and other plastic products have been discarded and dumped as garbage in the ocean, causing environmental pollution. These plastic products break down in seawater and become submicron-sized fragments (microplastics), which float in the seawater. If marine organisms such as fish ingest the plastics, they will accumulate in their bodies, raising concerns that they may affect the health of seabirds and humans who consume the marine organisms as food.

[0003] The plastic products mainly include food packaging packages using plastic substrates. In these packages, various plastic substrates such as polyester (PET), nylon (NY), and polypropylene (PP) substrates are used as film substrates. These plastic substrates are printed with gravure ink, flexographic ink, and other printing inks, and are then bonded to a sealant substrate via an adhesive or the like to form a laminate. The laminate is then cut and heat-sealed to form a package.

[0004] Attempts to reduce the amount of microplastics in the above-mentioned packaging include (1) replacing plastic base materials with "paper" made from wood, a renewable resource, (2) mono-materializing plastic base materials into a single material (polyolefin) and recycling them, and (3) removing impurities and recycling plastic base materials.

[0005] The above-mentioned (1) is promising in terms of safety and recyclability, but it is inferior in many aspects to conventional plastic substrates in terms of performance, such as gas barrier properties, water vapor barrier properties, and water resistance. Regarding (2) above, technology is being developed to cover the weaknesses of polyolefins with functional coating agents such as barrier coating agents, but since polyolefins are inferior in performance to conventional plastic substrates in terms of retort suitability, light blocking properties, etc., it is not easy to replace them with polyolefins. Furthermore, there is also the issue that inks, functional coating agents, adhesives, etc. between polyolefin substrates become impurities when recycling polyolefins.

[0006] As for (3) above, attempts have been made to remove the printed layer on the outer surface of the package, which becomes an impurity during the recycling process, with an alkaline aqueous solution. For example, Cited Document 1 discloses a technique in which an undercoat layer made of an acrylic resin or a styrene-maleic acid resin is provided on a plastic substrate, and a printed layer disposed on the undercoat layer is removed with alkaline water. Patent Document 2 discloses a technique in which an ink containing a polyurethane resin or an acrylic resin having an acidic group as a binder resin is printed, and the printed layer is removed with alkaline water. However, these techniques only remove the surface-printed ink on the outside of the package, and do not allow the sealant substrate to be peeled from the other substrates in the laminate.

[0007] A technology for peeling the sealant substrate from a packaging material in which a substrate including a plastic layer and a print layer and a sealant substrate are laminated with an adhesive, and recycling the sealant substrate, which is particularly thick and accounts for a large proportion of the entire packaging material, is an important technology that can be used industrially to promote the recycling of plastics and contribute to environmental conservation. However, no packaging material has yet been reported that has an adhesive layer that combines the required performance of a laminating adhesive with the function of peeling the sealant substrate from other substrates. [Prior art documents] [Patent documents]

[0008] [Patent Document 1] JP 2001-131484 A [Patent Document 2] Japanese Patent Application Publication No. 11-209677 Summary of the Invention [Problem to be solved by the invention]

[0009] An object of the present invention is to provide a packaging material that has excellent adhesive strength and boiling / retort resistance, and also has excellent separation / detachment properties of a substrate from the packaging material, and a packaging container formed from said packaging material. [Means for solving the problem]

[0010] The present invention relates to the following inventions [1] to [8].

[0011] [1] A packaging material having a configuration in which at least a first substrate, a printed layer, a polyurethane-based adhesive layer for removing the second substrate, and a second substrate are laminated in this order from the outer layer side, and the polyurethane-based adhesive layer is provided in contact with the second substrate.

[0012] [2] The packaging material according to [1], wherein the polyurethane-based adhesive layer is a cured product of an adhesive containing a polyol component and a polyisocyanate component, and the polyol component contains a polyester polyol.

[0013] [3] The packaging material according to [2], wherein the polyester polyol has a urethane bond.

[0014] [4] The packaging material according to [2] or [3], wherein the polyisocyanate component comprises at least one selected from the group consisting of aliphatic polyisocyanates and araliphatic polyisocyanates.

[0015] [5] The packaging material according to any one of [1] to [4], wherein the adhesive has an acid value of 5 to 45 mgKOH / g.

[0016] [6] The packaging material described in any one of [1] to [5], wherein the polyurethane-based adhesive layer further contains a phosphorus oxygen acid or a derivative thereof in an amount of 0.01 to 5 mass % based on the mass of the polyurethane-based adhesive layer.

[0017] [7] The packaging material according to any one of [1] to [6], wherein the polyurethane-based adhesive layer further contains fine particles having an average particle size of 1 to 10 μm.

[0018] [8] The packaging material according to [7], wherein the content of the fine particles is 0.1 to 10 mass % based on the mass of the polyurethane-based adhesive layer.

[0019] [9] The packaging material according to any one of [1] to [8], wherein the polyurethane adhesive layer has a thickness of 1 to 6 μm.

[0020]

[10] The packaging material according to any one of [1] to [9], wherein the second base material contains a polyolefin.

[0021]

[11] The packaging material according to any one of [1] to

[10] , wherein the second substrate is a layer formed by extrusion lamination, and the polyurethane-based adhesive layer has a thickness of 0.01 to 1 μm.

[0022]

[12] A packaging container, at least a portion of which is formed from the packaging material described in any one of [1] to

[10] . Effect of the Invention

[0023] The present invention can provide a packaging material that has excellent adhesive strength and boiling / retort resistance, and also has excellent separation / detachment properties of a substrate from the packaging material, and a packaging container formed from the packaging material. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0024] The packaging material of the present invention is a packaging material having a configuration in which at least a first substrate, a printed layer, a polyurethane-based adhesive layer for detaching the second substrate (hereinafter also referred to as a removable adhesive layer), and a second substrate are laminated in this order from the outer layer side, and is characterized in that the polyurethane-based adhesive layer is provided in contact with the second substrate. The packaging material allows the second substrate to be separated and recovered by detaching the polyurethane adhesive layer for detaching the second substrate from the second substrate. Therefore, the packaging material of the present invention corresponds to a packaging material used for separating and recovering the second substrate. The present invention will be described in detail below, but these are merely examples of the embodiments of the present invention, and the present invention is not limited to these details as long as it does not depart from the gist of the present invention.

[0025] <Polyurethane-based adhesive layer for removing the second substrate> "Detachment" in the case of a polyurethane-based adhesive layer for detaching from a second substrate refers to the adhesive layer being neutralized with a basic aqueous solution and dissolving or swelling, causing the printed layer to peel off from the second substrate, and includes both cases: (1) the polyurethane-based adhesive layer dissolves and causes the printed layer to peel off from the second substrate, and (2) the adhesive layer peels off from the second substrate due to dissolution, swelling, etc. of the polyurethane-based adhesive layer. Since the present invention aims to obtain the second substrate as a recycled substrate or a regenerated substrate, it is preferable that as much of the polyurethane adhesive layer as possible is removed from the second substrate. Specifically, it is preferable that at least 50% by mass or more of the polyurethane adhesive layer is removed in the area or thickness direction out of 100% by mass. It is more preferable that 60% by mass or more, even more preferably 80% by mass or more, and particularly preferably 90% by mass or more is removed.

[0026] The basic compound used in the basic aqueous solution is not particularly limited, and examples of the basic compound that can be used include, but are not limited to, sodium hydroxide (NaOH), potassium hydroxide (KOH), calcium hydroxide (Ca(OH)2), ammonia, barium hydroxide (Ba(OH)2), and sodium carbonate (Na2CO3). More preferably, the basic compound is at least one selected from the group consisting of sodium hydroxide and potassium hydroxide.

[0027] The mechanism of detachment is assumed to be that in a packaging material containing a polyurethane-based adhesive layer (for example, an embodiment such as first substrate / printed layer / polyurethane-based adhesive layer / second substrate), a basic aqueous solution penetrates through gaps between layers and comes into contact with the polyurethane-based adhesive layer, causing the polyurethane-based adhesive layer to dissolve, etc., resulting in detachment of substrate 2. Therefore, the detachment step is preferably carried out in a state in which the packaging material has been cut and the cross section has been exposed, i.e., in a state in which the polyurethane-based adhesive layer has been exposed.

[0028] The polyurethane-based adhesive layer in the present invention is in contact with the second substrate described below, and is provided for the purpose of detaching the second substrate, and separating and recovering the second substrate from the packaging material to obtain a recycled substrate. Therefore, solder resists, color resists, etc. are not only in completely different technical fields, but also have a different technical concept from the polyurethane-based adhesive layer of the present invention, as they aim to leave a certain amount of film after alkaline aqueous solution treatment.

[0029] <Adhesive for forming polyurethane-based adhesive layer> The polyurethane-based adhesive layer is not particularly limited as long as it is polyurethane-based, and is preferably a cured product of a two-component curing polyurethane-based adhesive containing a polyol component and a polyisocyanate component.

[0030] [Polyol component] The polyol component is not particularly limited and can be selected from conventionally known polyol components, and may be used alone or in combination of two or more kinds. The polyol component preferably contains a polyester polyol because the ester bond has a high affinity for an alkaline aqueous solution, which improves the releasing property. The polyester polyol is, but is not limited to, a dibasic acid such as terephthalic acid, isophthalic acid, naphthalenedicarboxylic acid, phthalic anhydride, adipic acid, azelaic acid, sebacic acid, succinic acid, glutaric acid, tetrahydrophthalic anhydride, hexahydrophthalic anhydride, maleic anhydride, itaconic anhydride, or a dialkyl ester thereof, or a mixture thereof (hereinafter also referred to as a carboxyl group component), For example, ethylene glycol, propylene glycol, diethylene glycol, dipropylene glycol, triethylene glycol, butylene glycol, neopentyl glycol, dineopentyl glycol, trimethylolpropane, glycerin, 1,6-hexanediol, 1,4-butanediol, 1,4-cyclohexanedimethanol, 3-methyl-1,5-pentanediol, 3,3'-dimethylolheptane, 1,9-nonanediol, polyoxyethylene glycol, polyoxypropylene glycol, polytetramethylene ether glycol, polyether polyol, polycarbonate polyol, polyolefin polyol, acrylic polyol, polyurethane polyol, or other diols or mixtures thereof (hereinafter also referred to as hydroxyl group components), or polyester polyols obtained by ring-opening polymerization of lactones such as polycaprolactone, polyvalerolactone, and poly(β-methyl-γ-valerolactone). The above carboxyl group components and hydroxyl group components may be used in combination of two or more kinds.

[0031] The polyester polyol preferably has a urethane bond and may be a polyester polyurethane polyol reacted with a diisocyanate. The polyester polyol and polyester polyurethane polyol may be further reacted with an acid anhydride. Examples of diisocyanates include 2,4-tolylene diisocyanate, 2,6-tolylene diisocyanate, xylylene diisocyanate, diphenylmethane diisocyanate, isophorone diisocyanate, 1,5-naphthalene diisocyanate, hexamethylene diisocyanate, and hydrogenated diphenylmethane diisocyanate. Examples of the acid anhydride include pyromellitic anhydride, mellitic anhydride, trimellitic anhydride, trimellitic ester anhydride, etc. Examples of the trimellitic ester anhydride include ethylene glycol bisanhydrotrimellitate, propylene glycol bisanhydrotrimellitate, etc.

[0032] Among them, the polyester polyol preferably contains an acid anhydride modified polyester polyurethane polyol. The polyester polyol component has a urethane bond, and thus can exhibit excellent heat resistance and adhesiveness. When the polyester polyol is an acid anhydride modified polyester polyol, it is possible to finely control the acid value, and it is preferable to easily obtain a polyester polyol having a suitable acid value range as described below.

[0033] The adhesive for forming the polyurethane adhesive layer preferably has an acid value. When the adhesive has an acid value, the second substrate is easily peeled off in a basic aqueous solution due to the neutralization with the alkali. Therefore, it is preferable that the polyester polyol has an acid value, and the acid value of the polyester polyol is preferably 8 mgKOH / g or more, more preferably 10 mgKOH / g or more. In addition, the acid value of the polyester polyol is preferably 45 mgKOH / g or less. When the polyester polyol has the above acid value, the adhesive layer formed from the adhesive containing the polyester polyol exhibits excellent releasability while maintaining adhesive strength, and is optimal for recycling the second substrate from the packaging material. When the polyester polyol contains a plurality of polyester polyols, the acid value of the polyester polyol can be determined from the acid value of each polyester polyol and the mass ratio thereof.

[0034] From the viewpoint of heat sterilization resistance of the adhesive layer and coatability, the number average molecular weight (Mn) of the polyester polyol mixture is preferably 3,000 to 20,000, more preferably 5,000 to 15,000, and particularly preferably 7,000 to 12,000. If the number average molecular weight (Mn) of the polyester polyol is 3,000 or more, not only coatability but also sufficient retort suitability can be exhibited, and if it is 20,000 or less, not only coatability but also releasability is improved, so this is preferable. The number average molecular weight in this specification is a value calculated in terms of standard polystyrene using a GPC (gel permeation chromatography) "Shodex GPC System-21" manufactured by Showa Denko KK and tetrahydrofuran as a solvent.

[0035] In order to satisfy various physical properties required for the packaging material, multiple polyester polyols may be used in combination. In such a case, the number average molecular weight of the polyester polyol component can be determined from the number average molecular weights of each polyester polyol and their mass ratio. Each polyester polyol component preferably contains a polyester polyol having a number average molecular weight of 5,000 to 15,000, and further preferably contains a polyester polyol having a number average molecular weight of less than 3,000 in order to improve adhesion to the substrate. The content of the polyester polyol having a number average molecular weight of less than 3,000 is preferably 0 to 30% by mass, and more preferably 0 to 20% by mass, based on the total amount of the polyester polyol component. When it is 30% by mass or less, retort resistance is not reduced, which is preferable.

[0036] From the viewpoint of adhesive performance and releasability, the polyester polyol may contain the following three types of polyols. First polyol: polyester polyol having an acid value of 10 mg / KOH or more Second polyol: polyester polyol having a number average molecular weight of less than 3,000 The third polyol: a polyester polyol having a number average molecular weight of 5,000 or more (However, this does not include the case where the second polyol and the third polyol are the first polyol component.)

[0037] The first polyol component has a role of imparting releasability, the second polyol component improves adhesion to the substrate and contributes to improving coatability, and the third polyol component has a role of improving retort properties. The content of the first polyol component is preferably 50% by mass or more based on the total amount of the polyester polyol component in order to exhibit sufficient releasability. The first polyol component is preferably a polyester polyurethane polyol modified with an acid anhydride, and more preferably has a number average molecular weight of 5,000 to 10,000 and an acid value of 15 to 40 mgKOH / g. The second polyol component preferably has an acid value of 5 mg KOH / g or less, more preferably 1 mg KOH / g or less. The third polyol component is preferably a polyester polyurethane polyol modified with an acid anhydride, and more preferably has a number average molecular weight of 5,000 or more and 10,000 or less, and an acid value of 5 mgKOH / g or less.

[0038] (Other polyols) The adhesive of the present invention may contain other polyols besides the polyester polyols. The polyols that may be contained other than the polyester polyols are not particularly limited, and examples thereof include polycarbonate polyols, polycaprolactone polyols, polyether polyols, polyolefin polyols, acrylic polyols, silicone polyols, castor oil-based polyols, and fluorine-based polyols. These may be used alone or in combination of two or more kinds.

[0039] [Polyisocyanate component] The polyisocyanate component is not particularly limited and can be selected from conventionally known polyisocyanates, and preferably contains at least one polyisocyanate component selected from the group consisting of aliphatic polyisocyanates and araliphatic polyisocyanates. These may be used alone or in combination of two or more kinds.

[0040] (Aliphatic polyisocyanate) The aliphatic polyisocyanate is not limited to the following, but may be a compound derived from a well-known aliphatic diisocyanate or alicyclic diisocyanate. Examples of aliphatic polyisocyanates that can be used in the present invention include aliphatic diisocyanates such as trimethylene diisocyanate, tetramethylene diisocyanate, hexamethylene diisocyanate, 1,2-propylene diisocyanate, 1,2-butylene diisocyanate, 2,3-butylene diisocyanate, 1,3-butylene diisocyanate, 2,4,4- or 2,2,4-trimethylhexamethylene diisocyanate, and 2,6-diisocyanate methyl caproate; Alicyclic diisocyanates such as 1,4-cyclohexane diisocyanate, 1,3-cyclohexane diisocyanate, 3-isocyanatomethyl-3,5,5-trimethylcyclohexyl isocyanate, 4,4'-methylenebis(cyclohexyl isocyanate), methyl 2,4-cyclohexane diisocyanate, methyl 2,6-cyclohexane diisocyanate, 1,4-bis(isocyanatomethyl)cyclohexane, and 1,3-bis(isocyanatomethyl)cyclohexane; Alternatively, polyisocyanates such as allophanate type, nurate type, biuret type, and adduct type derivatives derived from the above-mentioned aliphatic diisocyanates or alicyclic diisocyanates, or complexes thereof; and the like. The derivatives are preferably nurate type and adduct type derivatives, and more preferably adduct type derivatives. A preferred aliphatic polyisocyanate is a polyisocyanate derived from hexamethylene diisocyanate (hereinafter referred to as HDI), which can easily ensure a balance between releasability and laminate properties.

[0041] (Aromatic aliphatic polyisocyanate) The araliphatic polyisocyanate is not limited to the following, but a compound derived from a well-known araliphatic diisocyanate can be used. The aromatic aliphatic polyisocyanates that can be used in the present invention include aromatic aliphatic diisocyanates such as 1,3- or 1,4-xylylene diisocyanate or a mixture thereof, ω,ω'-diisocyanato-1,4-diethylbenzene, 1,3- or 1,4-bis(1-isocyanato-1-methylethyl)benzene or a mixture thereof; Alternatively, polyisocyanates such as derivatives of the above-mentioned araliphatic diisocyanates or complexes thereof may be used.

[0042] (Other polyisocyanate components) The adhesive may contain other polyisocyanates in addition to the above-mentioned aliphatic polyisocyanates and araliphatic polyisocyanates. Examples of other polyisocyanates include aromatic diisocyanates such as toluene diisocyanate and diphenylmethane diisocyanate, and polyisocyanates such as derivatives of the above-mentioned diisocyanates or complexes thereof. The derivative is preferably an adduct type derivative.

[0043] <Adhesive manufacturing> The adhesive for forming the polyurethane-based adhesive layer may further contain other components. The other components may be blended with either the polyol component or the polyisocyanate component, or may be added when blending the polyol component and the polyisocyanate component.

[0044] [Other ingredients] (Silane coupling agent) The adhesive may further contain a silane coupling agent to enhance hot water resistance. Examples of the silane coupling agent include trialkoxysilanes having a vinyl group, such as vinyltrimethoxysilane and vinyltriethoxysilane, trialkoxysilanes having an amino group, such as 3-aminopropyltriethoxysilane and N-(2-aminoethyl)3-aminopropyltrimethoxysilane, and trialkoxysilanes having a glycidyl group, such as 3-glycidoxypropyltrimethoxysilane, 2-(3,4-epoxycyclohexyl)ethyltrimethoxysilane and 3-glycidoxypropyltriethoxysilane. The amount of the silane coupling agent added is preferably 0.1 to 5 mass%, more preferably 0.5 to 3 mass%, based on the solid content of the adhesive.

[0045] (Phosphorus oxygen acid or its derivatives) The adhesive may further contain a phosphorus oxyacid or a derivative thereof in order to enhance acid resistance. Among the phosphorus oxyacids or derivatives thereof, the phosphorus oxyacid may be any one having at least one free oxyacid, and examples thereof include phosphoric acids such as hypophosphorous acid, phosphorous acid, orthophosphoric acid, and hypophosphoric acid, and condensed phosphoric acids such as metaphosphoric acid, pyrophosphoric acid, tripolyphosphoric acid, polyphosphoric acid, and ultraphosphoric acid. In addition, examples of derivatives of phosphorus oxyacids include those partially esterified with alcohols in a state in which at least one free oxyacid remains. Examples of these alcohols include aliphatic alcohols such as methanol, ethanol, ethylene glycol, and glycerin, and aromatic alcohols such as phenol, xylenol, hydroquinone, catechol, and phloroglucinol. Two or more types of phosphorus oxyacids or derivatives thereof may be used in combination. The amount of phosphorus oxyacid or its derivative added is preferably 0.01 to 10 mass %, more preferably 0.05 to 5 mass %, and particularly preferably 0.1 to 1 mass %, based on the solid content of the adhesive.

[0046] The adhesive may contain the above-mentioned phosphorus oxygen acid or a derivative thereof in order to improve the releasability of the second substrate and increase the recyclability of the second substrate. From the viewpoint of the strength and releasability of the packaging material, the content of the phosphorus oxygen acid or a derivative thereof is preferably 0.01 to 5 mass% based on the solid content of the adhesive. That is, the polyurethane adhesive layer contains the phosphorus oxygen acid or a derivative thereof in the range of preferably 0.01 to 5 mass% based on the mass of the polyurethane adhesive layer. More specifically, the amount of phosphorus oxyacid is more preferably 0.01 to 1 mass% based on the solid content of the adhesive, and even more preferably 0.01 to 0.5 mass%. When the amount is 0.01 mass% or more, the strength of the packaging material is maintained while the releasability is improved. When the amount is 1 mass% or less, the strength of the packaging material is excellent. The amount of the phosphoric acid derivative is preferably 0.01 to 5 mass %, more preferably 0.1 to 3 mass %, based on the solid content of the adhesive. When the amount is 0.01 mass % or more, the strength of the packaging material is maintained while the releasability is improved. When the amount is 5 mass % or less, the strength as a packaging material is excellent.

[0047] (Leveling agent or defoamer) The adhesive may further contain a leveling agent or a defoaming agent to improve the appearance of the laminate. Examples of the leveling agent include polyether-modified polydimethylsiloxane, polyester-modified polydimethylsiloxane, aralkyl-modified polymethylalkylsiloxane, polyester-modified hydroxyl-containing polydimethylsiloxane, polyetherester-modified hydroxyl-containing polydimethylsiloxane, acrylic copolymer, methacrylic copolymer, polyether-modified polymethylalkylsiloxane, acrylic acid alkyl ester copolymer, methacrylic acid alkyl ester copolymer, and lecithin. Examples of the defoaming agent include known ones such as silicone resin, silicone solution, copolymers of alkyl vinyl ether, alkyl acrylate, and alkyl methacrylate.

[0048] (Reaction accelerator) The adhesive may further contain a reaction accelerator to accelerate the urethane reaction. Examples of the reaction accelerator include metal catalysts such as dibutyltin diacetate, dibutyltin dilaurate, dioctyltin dilaurate, and dibutyltin dimaleate; tertiary amines such as 1,8-diaza-bicyclo(5,4,0)undecene-7, 1,5-diazabicyclo(4,3,0)nonene-5, and 6-dibutylamino-1,8-diazabicyclo(5,4,0)undecene-7; and reactive tertiary amines such as triethanolamine. One or more reaction accelerators selected from these groups may be used.

[0049] The adhesive may contain various additives within a range that does not impair the effects of the present invention. Examples of additives include inorganic fillers such as silica, alumina, mica, talc, aluminum flakes, and glass flakes, layered inorganic compounds, stabilizers (antioxidants, heat stabilizers, ultraviolet absorbers, hydrolysis inhibitors, etc.), rust inhibitors, thickeners, plasticizers, antistatic agents, lubricants, antiblocking agents, colorants, fillers, crystal nucleating agents, and catalysts for adjusting the curing reaction.

[0050] In addition, the adhesive may contain fine particles having an average particle size of 1 to 10 μm as the additive described above in order to improve the releasability and increase the recyclability of the second substrate. It is presumed that the inclusion of such fine particles maintains the strength of the packaging material due to an anchoring effect on the substrate, while reducing the contact area between the adhesive and the substrate, thereby improving the releasability. When the average particle size is 1 μm or more, the strength of the packaging material is maintained while improving the release property. When the average particle size is 10 μm or less, the strength of the packaging material can be maintained. In this specification, the average particle size means the median size measured by a particle size distribution measuring device using a laser diffraction / scattering method. The fine particles having an average particle size of 1 to 10 μm are not particularly limited, and examples thereof include inorganic fillers such as silica, alumina, mica, talc, aluminum flakes, and glass flakes, as well as aluminum hydroxide, precipitated barium sulfate, magnesium carbonate, calcium carbonate, zeolite, and resin beads such as acrylic beads and urethane beads.

[0051] From the viewpoint of the strength and releasability of the packaging material, the blending amount of the fine particles is preferably 0.1 to 10 mass %, more preferably 0.5 to 5.0 mass %, based on the solid content of the adhesive. That is, the polyurethane adhesive layer in the present invention contains fine particles having an average particle size of 1 to 10 μm in an amount of preferably 0.1 to 10 mass %, more preferably 0.5 to 5.0 mass %, based on the mass of the polyurethane adhesive layer. When the content is 0.5% by mass or more, the strength of the packaging material is maintained while the releasability is improved, and when the content is 5.0% by mass or less, the strength as a packaging material is excellent.

[0052] The polyurethane adhesive layer preferably contains both the phosphorus oxyacid or its derivative and the fine particles having an average particle size of 1 to 10 μm, which improves the releasability and removal rate.

[0053] The adhesive can be used as a solvent-free type when its viscosity is 100 to 10,000 mPa·s, preferably 100 to 5,000 mPa·s at room temperature to 150°C, preferably room temperature to 100°C. If the viscosity of the adhesive is higher than the above range, it may be diluted with an organic solvent. As the organic solvent, for example, esters such as ethyl acetate, ketones such as methyl ethyl ketone, aromatic hydrocarbons such as toluene and xylene, etc., which are inactive to the polyisocyanate component, are suitably used, and can be appropriately selected and used.

[0054] The acid value immediately after mixing of the adhesive for forming the polyurethane adhesive layer for removing the second substrate is preferably 5 mgKOH / g or more, more preferably 7 mgKOH / g or more, even more preferably 10 mgKOH / g or more, and particularly preferably 20 mgKOH / g or more. The acid value immediately after mixing of the adhesive is preferably 45 mgKOH / g or less, more preferably 40 mgKOH / g or less, and even more preferably 35 mgKOH / g or less. When the acid value is 5 mgKOH / g or more, the second substrate can be easily peeled off in a basic aqueous solution. When the acid value is 45 mgKOH / g or less, the adhesive layer has good adhesion and water resistance. Therefore, when the acid value is within the above range, it is preferable because the adhesive layer exhibits excellent detachment properties and can recover the sealant substrate while maintaining the adhesive strength and retort resistance required for a lamination adhesive.

[0055] When the polyol component and the polyisocyanate component are mixed, they are mixed so that the equivalent ratio (NCO / OH) of the isocyanate group of the polyisocyanate to the hydroxyl group of the polyol is 0.3 to 5.0, more preferably 0.3 to 2.0, and particularly preferably 0.5 to 1.5.

[0056] A typical method for forming a polyurethane-based adhesive layer includes forming a printed layer on a first substrate, applying the above-mentioned adhesive onto the printed layer, and optionally performing a drying process to volatilize the organic solvent, and then bonding the printed layer to a second substrate using a laminator and curing the layer at room temperature or under heating to form a polyurethane-based adhesive layer. In addition, when the second substrate is a substrate made of a sealant resin, the second substrate may be a layer formed by extrusion lamination. Examples of a method for laminating the second substrate by extrusion lamination include a method in which an adhesive is applied onto a printed layer of a laminate having a printed layer on a first substrate, and an organic solvent is evaporated through a drying process as necessary, and then the molten sealant resin is extruded by a T-die method, the second substrate is laminated by a cooling roll, and the second substrate is cured at room temperature or under heating to form a removable adhesive layer. There is no limit to the amount of adhesive applied after drying, usually 0.001 to 6 g / m 2 In the case of the solventless type, the range is preferably 1 to 2.5 g / m 2 , 1-6g / m for solvent-based 2 The thickness of the adhesive layer is not limited, and is usually in the range of 0.001 to 5 μm, preferably 1 to 2 μm for a solventless type and 1 to 5 μm for a solvent type. When the second base material is a layer formed by extrusion lamination, the coating amount of the adhesive after drying is preferably in the range of 0.01 to 1 μm, and more preferably in the range of 0.05 to 0.5 μm.

[0057] <First substrate> Examples of the first substrate include plastic films commonly used in packaging materials, gas barrier substrates such as metal foils, and paper. Examples of the plastic film include films of thermoplastic resins and thermosetting resins, and are preferably films of thermoplastic resins, such as polyolefins, polyesters, polyamides, polystyrenes, vinyl chloride resins, vinyl acetate resins, ABS resins, acrylic resins, acetal resins, polycarbonate resins, and cellulose-based plastics.

[0058] More specifically, polyester resin films such as polyethylene terephthalate, polyethylene naphthalate (PEN), and polylactic acid (PLA), polyolefin resin films such as polyethylene (PE) and polypropylene (PP), polystyrene resin films, polyamide resin films such as nylon 6 and poly-p-xylylene adipamide (MXD6 nylon), polycarbonate resin films, polyacrylonitrile resin films, polyimide resin films, laminates thereof (for example, nylon 6 / MXD6 / nylon 6, nylon 6 / ethylene-vinyl alcohol copolymer / nylon 6), and mixtures thereof are used. Among them, those having mechanical strength and dimensional stability are preferred. The thickness of the plastic film is preferably 5 μm or more and 200 μm or less, more preferably 10 μm or more and 100 μm or less, and further preferably 10 μm or more and 50 μm or less.

[0059] Examples of the gas barrier substrate include aluminum foil, plastic film having a vapor-deposited layer of aluminum, silica, alumina, etc. In the case of aluminum foil, a thickness in the range of 3 to 50 μm is preferable from an economical point of view.

[0060] <Print layer> The printed layer is a layer that forms any printed pattern for the purpose of decoration, imparting an aesthetic feel, displaying the contents, expiration date, manufacturer or seller, etc., and includes a solid printed layer. The printed layer can be provided, for example, between the substrate and the adhesive layer, and may be provided on the entire surface or part of the substrate. The printing layer can be formed using a conventionally known pigment or dye, or may be formed using a printing ink containing a pigment or dye, and the method of formation is not particularly limited. The printing layer may be formed of a single layer or multiple layers. The thickness of the printing layer is preferably 0.1 μm or more and 10 μm or less, more preferably 1 μm or more and 5 μm or less, and even more preferably 1 μm or more and 3 μm or less.

[0061] Examples of the printing ink for forming the printing layer include printing inks containing a medium such as a pigment, a binder, and a solvent or water. Examples of the binder that can be used include fibrous materials such as nitrocellulose, cellulose acetate propionate, and the like, chlorinated polypropylene, vinyl chloride-vinyl acetate copolymer, polyester, acrylic, polyurethane, and acrylic urethane, polyamide, polybutyral, cyclized rubber, chlorinated rubber, and a suitable combination of these.

[0062] The method for applying the printing ink is not particularly limited, and the printing ink can be applied by a method such as gravure coating, flexo coating, roll coating, bar coating, die coating, curtain coating, spin coating, inkjet coating, etc. The printing ink can be left as it is, or if necessary, subjected to air blowing, heating, drying under reduced pressure, ultraviolet irradiation, etc., to form a printing layer.

[0063] A primer layer may be formed between the first substrate and the printed layer as necessary in order to satisfy various requirements for packaging materials such as substrate adhesion, etc. As the primer layer, a conventionally known one can be used.

[0064] <Second substrate> The second substrate may be, for example, the substrate listed in the above-mentioned first substrate or a sealant substrate, preferably a sealant substrate containing polyolefin. The second substrate may have a vapor-deposited film of silica, alumina, or the like. Examples of sealant base materials include polyethylenes such as low-density polyethylene (LDPE), linear low-density polyethylene (LLDPE), and high-density polyethylene (HDPE), acid-modified polyethylene, polypropylene (PP), acid-modified polypropylene, copolymerized polypropylene, ethylene-vinyl acetate copolymer, ethylene-(meth)acrylic acid ester copolymer, ethylene-(meth)acrylic acid copolymer, and ionomer. From the viewpoint of recyclability, the second substrate is preferably a polyolefin such as polyethylene, such as low-density polyethylene, linear low-density polyethylene or high-density polyethylene, acid-modified polyethylene, polypropylene, acid-modified polypropylene or copolymer polypropylene. From the viewpoint of retort resistance, polypropylene is preferable, and from the viewpoint of heat sealability, unoriented polypropylene is preferable.

[0065] The thickness of the second substrate is not particularly limited, and is preferably 10 μm to 150 μm, more preferably 20 μm to 70 μm, in consideration of processability into packaging containers, heat sealability, etc. By providing the second substrate with irregularities having height differences of about several μm, slipperiness and tearability of the packaging material can be imparted. The method for laminating the second substrate is not particularly limited, and examples thereof include a method in which a laminated film having substrate 1 and a printed layer is bonded to the second substrate using a polyurethane-based adhesive for removing the second substrate; a method in which a resin constituting the second substrate is melted and extruded onto a polyurethane-based adhesive layer for removing the second substrate, and then cooled and solidified; and the like.

[0066] Examples of the configuration of the packaging material of the present invention are given below, but the present invention is not limited to these. Biaxially oriented polypropylene (OPP) / Printing layer / Polyurethane adhesive layer / Non-oriented polypropylene (CPP) OPP / printed layer / polyurethane adhesive layer / Al vapor deposition CPP (hereinafter VMCPP), OPP / printed layer / polyurethane adhesive layer / PE, Biaxially oriented nylon (hereinafter ONY) / Printing layer / Polyurethane adhesive layer / PE, ONY / printed layer / polyurethane adhesive layer / CPP, PET / printed layer / polyurethane adhesive layer / CPP, PET / printed layer / adhesive layer / ONY / polyurethane adhesive layer / CPP, Transparent vapor deposition PET / printed layer / adhesive layer / NY / polyurethane adhesive layer / CPP, PET / printed layer / adhesive layer / AL / polyurethane adhesive layer / CPP, PET / printed layer / adhesive layer / AL / polyurethane adhesive layer / PE, PET / printed layer / adhesive layer / ONY / adhesive layer / AL / polyurethane adhesive layer / CPP, PET / printed layer / adhesive layer / AL / adhesive layer / ONY / polyurethane adhesive layer / CPP, PET / printed layer / polyurethane adhesive layer / LDPE EXT , ONY / printed layer / polyurethane adhesive layer / LLDPE EXT , OPP / printed layer / polyurethane adhesive layer / LDPE EXT , OPP / printed layer / polyurethane adhesive layer / LLDPE EXT , PET / printed layer / adhesive layer / AL / polyurethane adhesive layer / LDPE EXT , PET / printed layer / adhesive layer / AL / polyurethane adhesive layer / LLDPE EXT

[0067] <Packaging container> The packaging container of the present invention is at least partially formed from the packaging material. By forming the packaging container from the packaging material, a packaging container having excellent releasability of the sealant base material and suitable for recycling can be obtained. The type and use of the packaging container of the present invention are not particularly limited, but it can be suitably used as, for example, a food container, a detergent container, a cosmetic container, a pharmaceutical container, etc. The shape of the packaging container is not limited, and it can be formed into a shape according to the contents, and it is suitably used as a pouch, etc.

[0068] <Recycled substrate manufacturing method> The method for producing a recycled substrate in the present invention includes a step of immersing a packaging material having a structure in which a first substrate, a printed layer, a polyurethane-based adhesive layer for removing the second substrate, and a second substrate are laminated in this order from the outer layer side, in a basic aqueous solution. More specifically, the method for producing a recycled substrate in the present invention includes a step of immersing the packaging material in a basic aqueous solution, and a step of peeling and recovering the second substrate from the packaging material.

[0069] The basic aqueous solution preferably contains a basic compound in an amount of 0.5 to 20 mass % of the entire basic aqueous solution, more preferably 1 to 15 mass %, and particularly preferably 3 to 15 mass %. When the concentration is within the above range, the basic aqueous solution can retain sufficient basicity to dissolve or swell the polyurethane adhesive layer and peel off the second substrate. The basic aqueous solution penetrates from the edge of the packaging material, contacts the polyurethane adhesive layer, and dissolves or swells it, separating the printed layer from the second substrate. Therefore, in order to efficiently proceed with the removal process, it is preferable that the packaging material is cut or crushed so that the polyurethane adhesive layer is exposed on the cross section when it is immersed in the basic aqueous solution. In such a case, the printed layer, substrate, etc. can be removed in a shorter time.

[0070] The temperature of the basic aqueous solution when the packaging material is immersed is preferably 25 to 120°C, more preferably 30 to 120°C, and particularly preferably 30 to 80°C. The immersion time in the basic aqueous solution is preferably 1 minute to 24 hours, more preferably 1 minute to 12 hours, and particularly preferably 1 minute to 6 hours. The amount of the basic aqueous solution used is preferably 100 to 1,000,000 times the mass of the packaging material, and in order to improve the desorption efficiency, it is preferable to stir or circulate the basic aqueous solution. The rotation speed is preferably 80 to 250 rpm, and more preferably 80 to 200 rpm.

[0071] The printed layer is peeled off from the packaging material to recover the second substrate, and the second substrate is then washed with water and dried to obtain a recycled substrate. The removal rate of the polyurethane adhesive layer on the surface of the second substrate is preferably 80% by mass or more, more preferably 90% by mass or more, and even more preferably 95% by mass or more.

[0072] Therefore, in the present invention, a recycled substrate of the second substrate can be obtained through the steps of immersing the packaging material in a basic aqueous solution, peeling off the printed layer to remove the second substrate, separating and recovering the second substrate, and washing and drying the second substrate. The obtained recycled substrate can be processed into pellets using an extruder or the like and reused as recycled resin. EXAMPLES

[0073] The present invention will be described in more detail below with reference to examples and comparative examples. In the examples and comparative examples, "parts" and "%" mean "parts by mass" and "% by mass" unless otherwise specified.

[0074] <Acid value measurement> Approximately 1 g of sample was precisely weighed and placed in a stoppered Erlenmeyer flask, and dissolved in 100 ml of a toluene / ethanol (volume ratio: toluene / ethanol = 2 / 1) mixture. Phenolphthalein test solution was added as an indicator and held for 30 seconds. After that, the solution was titrated with 0.1 N alcoholic potassium hydroxide solution until it turned a light pink color, and the acid value was calculated using the following formula. Acid value (mgKOH / g)=(5.611×a×F) / S S: Amount of sample collected (g) a: Amount of 0.1N alcoholic potassium hydroxide solution consumed (ml) F: Factor of 0.1N alcoholic potassium hydroxide solution

[0075] <Number average molecular weight (Mn)> The number average molecular weight (Mn) was measured using a GPC (gel permeation chromatography) "Shodex GPC System-21" manufactured by Showa Denko KK In the measurement, tetrahydrofuran was used as a solvent, and the value was calculated in terms of standard polystyrene.

[0076] <Production of water-based primer> The aqueous primer composition S15 described in JP 2017-114930 A was used as the aqueous primer. Specifically, in a reactor equipped with a thermometer, a stirrer, a reflux condenser, and a nitrogen gas inlet tube, 100 parts of poly(3-methyl-1,5-pentane adipate) diol (hereinafter "PMPA") having a number average molecular weight of 2,000, 40 parts of poly(3-methyl-1,5-pentane adipate) diol having a number average molecular weight of 1,000, 35 parts of polyethylene glycol (hereinafter "PEG") having a number average molecular weight of 2,000, 30 parts of 2,2-dimethylolpropionic acid (hereinafter "DMPA"), and 109.6 parts of isophorone diisocyanate (hereinafter "IPDI") were refluxed in 77.4 parts of methyl ethyl ketone (hereinafter "MEK") at 80°C for 6 hours while introducing nitrogen gas to obtain a terminal isocyanate prepolymer, which was then cooled to 40°C to obtain a solvent solution of the terminal isocyanate prepolymer. Next, the obtained terminal isocyanate prepolymer solution was gradually added at room temperature to a mixture of 14 parts of isophoronediamine (hereinafter referred to as "IPDA"), 8.6 parts of 2-hydroxyethylethylenediamine (hereinafter referred to as "AEA"), 1.0 part of dibutylamine (hereinafter referred to as "DBA"), and 699.9 parts of acetone, and the mixture was allowed to react at 80°C for 1 hour to obtain a solvent-based polyurethane resin solution. Next, 13.6 parts of 28% ammonia water and 777.3 parts of ion-exchanged water were gradually added to the above solvent-based polyurethane resin solution to neutralize and make it water-soluble, and then all of the MEK and acetone were distilled off under azeotropic conditions, and water was added to adjust the solid content, yielding a polyurethane resin with an acid value of 37.7 mgKOH / g, a solid content concentration of 30%, and a mass average molecular weight of 30,000. 65 parts of the obtained polyurethane resin, 2 parts of a styrene-maleic acid resin derivative ("SMA1440H" manufactured by Sartomer Corporation, 30% solids aqueous solution, ammonia neutralization of alcohol-modified styrene-maleic acid), 4 parts of a vinyl chloride emulsion ("Vinyblan 700" manufactured by Nissin Chemical Industry Co., Ltd., 30% solids aqueous solution, a copolymer of vinyl chloride and other double bond monomers), 24 parts of water, and 5 parts of isopropanol (hereinafter "IPA") were mixed and stirred for 30 minutes with a disper to obtain an aqueous primer.

[0077] <Production of polyol> (Production Example 1) Polyester polyol (P-1) In a reaction vessel equipped with a stirrer, a thermometer, a reflux condenser, a dropping tank and a nitrogen gas inlet tube, 830 parts of diethylene glycol and 870 parts of adipic acid were charged, and the temperature was raised to 240°C while stirring under a nitrogen stream to carry out an esterification reaction. After a predetermined amount of water was distilled and the reaction was continued until the acid value was 5 or less, the pressure was gradually reduced and a deglycolization reaction was carried out at 1 mmHg or less for 5 hours to obtain a polyester polyol. Next, the solution was diluted with ethyl acetate until the nonvolatile content was 50%, to obtain a solution of polyester polyol (P-1) with a number average molecular weight of 2,300 and an acid value of 0.7 mgKOH / g.

[0078] (Production Example 2) Polyester polyol (P-2) In a reaction vessel equipped with a stirrer, a thermometer, a reflux condenser, a dropping tank and a nitrogen gas inlet tube, 279 parts of ethylene glycol, 242 parts of neopentyl glycol, 189 parts of 1,6-hexanediol, 81 parts of terephthalic acid, 710 parts of isophthalic acid and 218 parts of adipic acid were charged, and the mixture was heated to 250°C while stirring under a nitrogen stream to carry out an esterification reaction. After a predetermined amount of water was distilled and the reaction was continued until the acid value was 5 or less, the pressure was gradually reduced and a deglycolization reaction was carried out at 1 mmHg or less for 5 hours to obtain a polyester polyol. Then, 2 parts of isophorone diisocyanate was gradually added, and the reaction was carried out at 150°C for about 2 hours to obtain a polyester polyurethane polyol. 2.5 parts of trimellitic anhydride were added to 100 parts of this polyester polyurethane polyol and reacted at 180°C for approximately 2 hours. The mixture was then diluted with ethyl acetate until the non-volatile content reached 50%, yielding a solution of partially acid-modified polyester polyol (P-2) with a number average molecular weight of 6,000 and an acid value of 14.6 mg KOH / g.

[0079] (Production Example 3) Polyester polyol (P-3) A reaction vessel equipped with a stirrer, a thermometer, a reflux condenser, a dropping tank and a nitrogen gas inlet tube was charged with 142 parts of ethylene glycol, 156 parts of diethylene glycol, 148 parts of neopentyl glycol, 350 parts of 1,6-hexanediol, 437 parts of terephthalic acid, 437 parts of isophthalic acid and 192 parts of adipic acid, and the mixture was heated to 250°C while stirring under a nitrogen stream to carry out an esterification reaction. After a predetermined amount of water was distilled and the reaction was continued until the acid value was 5 or less, the pressure was gradually reduced and a deglycolization reaction was carried out at 1 mmHg or less for 5 hours to obtain a polyester polyol. 0.5 parts of trimellitic anhydride was added to 100 parts of this polyester polyol, and the mixture was reacted at 180°C for about 2 hours, and then diluted with ethyl acetate until the non-volatile content was 50%, to obtain a solution of partially acid-modified polyester polyol (P-3) with a number average molecular weight of 7,500 and an acid value of 3.1 mgKOH / g.

[0080] (Production Example 4) Polyester polyol (P-4) In a reaction vessel equipped with a stirrer, a thermometer, a reflux condenser, a dropping tank and a nitrogen gas inlet tube, 168 parts of ethylene glycol, 312 parts of neopentyl glycol, 217 parts of 1,6-hexanediol, 89 parts of terephthalic acid, 568 parts of isophthalic acid and 345 parts of sebacic acid were charged, and the temperature was raised to 250°C while stirring under a nitrogen stream to carry out an esterification reaction. After a predetermined amount of water was distilled and the reaction was continued until the acid value was 5 or less, the pressure was gradually reduced and a deglycolization reaction was carried out at 1 mmHg or less for 5 hours to obtain a polyester polyol. Then, 20 parts of isophorone diisocyanate was gradually added, and the reaction was carried out at 150°C for about 2 hours to obtain a polyester polyurethane polyol. 3.0 parts of ethylene glycol bis-anhydrotrimellitate were added to 100 parts of this polyester polyurethane polyol and reacted at 180°C for approximately 2 hours. The mixture was then diluted with ethyl acetate until the non-volatile content reached 50%, yielding a solution of partially acid-modified polyester polyol (P-4) with a number average molecular weight of 8,000 and an acid value of 8.5 mg KOH / g.

[0081] (Production Example 5) Polyester polyol (P-5) In a reaction vessel equipped with a stirrer, a thermometer, a reflux condenser, a dropping tank and a nitrogen gas inlet tube, 124 parts of ethylene glycol, 212 parts of neopentyl glycol, 368 parts of 1,6-hexanediol, 645 parts of isophthalic acid, 36 parts of adipic acid and 265 parts of sebacic acid were charged, and the mixture was heated to 250°C while stirring under a nitrogen stream to carry out an esterification reaction. After a predetermined amount of water was distilled and the reaction was continued until the acid value was 5 or less, the pressure was gradually reduced and a deglycolization reaction was carried out at 1 mmHg or less for 5 hours to obtain a polyester polyol. Then, 35 parts of isophorone diisocyanate was gradually added, and the reaction was carried out at 150°C for about 2 hours to obtain a polyester polyurethane polyol. 12.0 parts of ethylene glycol bis-anhydrotrimellitate were added to 100 parts of this polyester polyurethane polyol and reacted at 180°C for approximately 2 hours. The mixture was then diluted with ethyl acetate until the non-volatile content reached 50%, yielding a solution of partially acid-modified polyester polyol (P-5) with a number average molecular weight of 9,000 and an acid value of 30.3 mg KOH / g.

[0082] (Production Example 6) Polyester polyol (P-6) In a reaction vessel equipped with a stirrer, a thermometer, a reflux condenser, a dropping tank and a nitrogen gas inlet tube, 58 parts of ethylene glycol, 412 parts of diethylene glycol, 343 parts of neopentyl glycol, 517 parts of isophthalic acid and 393 parts of adipic acid were charged, and the mixture was heated to 250°C while stirring under a nitrogen stream to carry out an esterification reaction. After a predetermined amount of water was distilled and the reaction was continued until the acid value was 5 or less, the pressure was gradually reduced and a deglycolization reaction was carried out at 1 mmHg or less for 5 hours to obtain a polyester polyol. 4.0 parts of trimellitic anhydride were added to 100 parts of this polyester polyol, and the mixture was reacted at 180°C for about 2 hours, and then diluted with ethyl acetate until the non-volatile content was 50%, to obtain a solution of partially acid-modified polyester polyol (P-6) with a number average molecular weight of 2,000 and an acid value of 23.5 mgKOH / g.

[0083] (Production Example 7) Polyether polyol (P-7) A reaction vessel equipped with a stirrer, a thermometer, a reflux condenser, a dropping tank, and a nitrogen gas inlet tube was charged with 57 parts of P-2000 (trade name, manufactured by ADEKA Corporation, bifunctional polyoxypropylene glycol, hydroxyl value 56.1), 247 parts of P-400 (trade name, manufactured by ADEKA Corporation, bifunctional polyoxypropylene glycol, hydroxyl value 265.9), 57 parts of T-400 (trade name, manufactured by Mitsui Chemicals, Inc., trifunctional polyoxypropylene glycol, hydroxyl value 404), 12 parts of dimethylolpropionic acid, 207 parts of ethyl acetate, 118 parts of tolylene diisocyanate, and 0.102 parts of dibutyltin laurate, and the mixture was heated to 90° C. and reacted until the peak of the isocyanate group disappeared in the infrared absorption spectrum. Next, the solution was diluted with ethyl acetate to a non-volatile content of 50%, thereby obtaining a solution of partially acid-modified polyether polyol (P-7) having a number average molecular weight of 8,500 and an acid value of 10.2 mgKOH / g.

[0084] [Table 1]

[0085] <Adjustment of polyisocyanate> (Production Example 8) Polyisocyanate (C-1) Coronate 2785 (biuret type polyisocyanate derived from hexamethylene diisocyanate, manufactured by Tosoh Corporation) was diluted with ethyl acetate and adjusted to a non-volatile content of 50% and NCO% of 9.6%, to obtain a solution of polyisocyanate (C-1).

[0086] (Production Example 9) Polyisocyanate (C-2) Bestanat T1890 / 100 (nurate type polyisocyanate derived from isophorone diisocyanate (hereinafter, IPDI), manufactured by Evonik Corporation) was diluted with ethyl acetate and adjusted to a non-volatile content of 50% and NCO% of 8.7%, to obtain a solution of polyisocyanate (C-2).

[0087] (Production Example 10) Polyisocyanate (C-3) Takenate D-110NB (trimethylolpropane adduct type polyisocyanate derived from xylylene diisocyanate (hereinafter, XDI), manufactured by Mitsui Chemicals) was diluted with ethyl acetate and adjusted to a non-volatile content of 50% and NCO% of 7.9%, to obtain a solution of polyisocyanate (C-3).

[0088] (Production Example 11) Polyisocyanate (C-4) Coronate L (a trimethylolpropane adduct type polyisocyanate derived from toluene diisocyanate (hereinafter, TDI), manufactured by Tosoh Corporation) was diluted with ethyl acetate and adjusted to a non-volatile content of 50% and NCO% of 8.8%, to obtain a solution of polyisocyanate (C-4).

[0089] (Production Example 12) Polyisocyanate (C-5) Millionate MR-200 (a polymeric polyisocyanate derived from diphenylmethane diisocyanate (hereinafter, MDI), manufactured by Tosoh Corporation) was diluted with ethyl acetate and adjusted to a non-volatile content of 50% and an NCO% of 15.5%, to obtain a solution of polyisocyanate (C-5).

[0090] <Adhesive manufacturing> (Adhesive 1-11) The polyol solutions and polyisocyanate solutions obtained in the above Production Examples 1 to 7 were mixed in the ratios (mass ratios) shown in Table 2, and ethyl acetate was added to prepare adhesive solutions with a non-volatile content of 30 mass %.

[0091] [Table 2]

[0092] (Adhesive 12~23) The polyol solutions, polyisocyanate solutions, and other components obtained in Production Examples 1 to 7 above were mixed in the ratios (mass ratios) shown in Table 5, and ethyl acetate was added to prepare adhesive solutions with a non-volatile content of 30 mass %.

[0093] [Table 5]

[0094] The abbreviations in Table 5 are as follows: Phosphoric acid: 85% phosphoric acid aqueous solution Phosphoric acid derivative: Phosphanol RL-310, manufactured by Toho Chemical Industry Co., Ltd. Aluminum hydroxide 1: BF013, manufactured by Nippon Light Metal Co., Ltd., average particle size 1 μm Aluminum hydroxide 2: BX103, manufactured by Nippon Light Metal Co., Ltd., average particle size 5 μm Aluminum hydroxide 3: BF083, manufactured by Nippon Light Metal Co., Ltd., average particle size 10 μm Acrylic resin beads: Art Pearl J-7P, manufactured by Negami Chemical Industries, Ltd., average particle size 6 μm

[0095] <Manufacturing of packaging materials> [Example 1] Packaging material 1 Printing ink (Toyo Ink Co., Ltd., Rio Alpha R631 white) was diluted with an ethyl acetate / IPA mixed solvent (mass ratio 70 / 30) so that the viscosity was 16 seconds (25°C, Zahn cup No. 3). The diluted printing ink was printed on a corona-treated OPP film with a thickness of 20 μm at a printing speed of 50 m / min using a gravure proofing machine equipped with a solid plate with a plate depth of 35 μm, and then dried at 50°C to obtain an OPP / printed layer laminate. The thickness of the printed layer was 1 μm. Next, the adhesive 1 was applied to the printed layer of the obtained laminate using a laminator, and the solvent was evaporated, and then the applied surface was attached to a 25 μm-thick CPP film that had been subjected to a surface corona discharge treatment. The thickness of the adhesive layer was 2 μm. The obtained laminate was then kept at 40° C. for 4 days to obtain a packaging material 1 having a structure of OPP (20 μm) / printed layer (1 μm) / detachable adhesive layer (2 μm) / CPP (25 μm).

[0096] [Examples 2 to 8, Comparative Examples 1 to 3] Packaging Materials 2 to 8, 16 to 18 Packaging materials 2 to 8 and 16 to 18 were obtained in the same manner as packaging material 1, except that the adhesive and printing ink were changed to those shown in Table 3.

[0097] [Examples 9 to 11] Packaging Materials 9 to 11 Packaging materials 9 to 11 were obtained in the same manner as packaging material 1, except that the first substrate, printing ink, second substrate, detachable adhesive, and thickness of the detachable adhesive layer were changed as shown in Table 3.

[0098] [Example 12] Packaging material 12 Printing ink (Toyo Ink Co., Ltd., Rio Alpha R631 white) was diluted with an ethyl acetate / IPA mixed solvent (mass ratio 70 / 30) so that the viscosity was 16 seconds (25°C, Zahn cup No. 3). The diluted printing ink was printed on the deposition layer side of a transparent deposition PET film (Toppan Printing Co., Ltd., GL-ARH, thickness 12 μm) using a gravure proofing machine equipped with a solid plate with a plate depth of 35 μm at a printing speed of 50 m / min, and then dried at 50°C to obtain a PET / deposition layer / printed layer laminate. The thickness of the printed layer was 1 μm. Next, the adhesive 11 was applied onto the printed layer of the obtained laminate using a laminator, and after the solvent was evaporated, the applied surface was attached to a nylon film having a thickness of 15 μm. The thickness of the adhesive layer was 3 μm. Next, the adhesive 8 was applied to the nylon film surface of the obtained laminate using a laminator, and the solvent was evaporated, and then the applied surface was attached to a 70 μm-thick CPP film that had been subjected to a surface corona discharge treatment. The thickness of the removable adhesive layer was 3 μm. The obtained laminate was then kept at 40°C for 4 days to obtain a packaging material having a structure of PET-deposited layer (12 μm) / printed layer (1 μm) / adhesive layer (3 μm) / NY (15 μm) / detachable adhesive layer (3 μm) / CPP (70 μm).

[0099] [Examples 13 and 14] Packaging materials 13 and 14 Packaging materials 13 and 14 were obtained in the same manner as packaging material 12, except that the substrate and release adhesive were changed as shown in Table 3.

[0100] [Example 15] Packaging material 15 The above-mentioned water-based primer and printing ink (Rio Alpha R631 White, manufactured by Toyo Ink Co., Ltd.) were each diluted with an ethyl acetate / IPA mixed solvent (mass ratio 70 / 30) to a viscosity of 16 seconds (25° C., Zahn cup No. 3). A diluted water-based primer and a diluted printing ink were printed in that order on a 20 μm-thick corona-treated OPP film using a gravure proofing two-color machine equipped with a solid plate with a plate depth of 35 μm at a printing speed of 50 m / min, and then each unit was dried at 50° C. to obtain an OPP / primer layer / printed layer laminate. The thickness of the primer layer and the printed layer were each 1 μm. Next, the adhesive 1 was applied to the printed layer of the obtained laminate using a laminator, and the solvent was evaporated, and then the applied surface was laminated to a 40 μm-thick LLDPE film that had been subjected to a surface corona discharge treatment. The thickness of the removable adhesive layer was 3 μm. The obtained laminate was kept at 40° C. for 4 days to obtain a packaging material having a structure of OPP / primer layer / printed layer / removable adhesive layer / LLDPE.

[0101] [Example 16] Packaging material 19 Packaging material 19 was obtained in the same manner as packaging material 8, except that the second substrate was changed to a CPP film having a thickness of 30 μm and having been subjected to a surface corona discharge treatment.

[0102] [Examples 17 to 28] Packaging materials 20 to 31 Packaging materials 20 to 31 were obtained in the same manner as packaging material 19, except that the adhesive was changed to one shown in Table 6.

[0103] [Example 29] Packaging material 32 Printing inks (Toyo Ink Co., Ltd., Rio Alpha R39 indigo, R631 white) were each diluted with an ethyl acetate / IPA mixed solvent (mass ratio 70 / 30) so that the viscosity was 16 seconds (25°C, Zahn cup No. 3). Each diluted printing ink was printed in the order of indigo and white on a corona-treated PET film (PET) with a thickness of 12 μm using a gravure proofing two-color machine equipped with a solid plate with a plate depth of 35 μm. The printing speed was 50 m / min, and drying was performed at 50°C in each unit to obtain a PET / printed layer laminate. The thickness of the printed layer was 2 μm in total, with 1 μm indigo and 1 μm white. Next, the obtained laminate was sent out from the first roll, and adhesive 3 was applied onto the printed layer using a gravure coater, and the solvent was evaporated to form a removable adhesive layer having a thickness of 0.3 μm. Next, extrusion polyethylene (LDPE EXT ) was extruded at 315°C, and the laminate was wound up after cooling on a cooling roll. The obtained laminate was kept at 40°C for 4 days, and the laminate was mixed to obtain a laminate of PET (12 μm) / printing layer (2 μm) / removable adhesive layer (0.3 μm) / LDPE. EXT A packaging material 32 having a structure of (35 μm) was obtained.

[0104] [Examples 30 and 31] Packaging materials 33 and 34 Packaging materials 33 and 34 were obtained in the same manner as packaging material 32, except that the adhesive was changed to the adhesive shown in Table 7.

[0105] <Evaluation of packaging materials 1-18> The following evaluations were carried out using the obtained packaging materials 1 to 18. The results are shown in Tables 3 and 4.

[0106] (Adhesive strength: initial) Test pieces measuring 15 mm x 300 mm were prepared from packaging materials 1 to 18, and the laminate strength (N / 15 mm) between both substrates in contact with the polyurethane-based removable adhesive layer was measured using a tensile tester at a temperature of 20°C and a relative humidity of 65% using a T-type peeling speed of 30 cm / min.

[0107] (Adhesive strength: after boiling) A pouch measuring 21 cm x 30 cm was prepared using the packaging material 9, and a sauce containing salad oil, ketchup, and 4.2% vinegar in a mass ratio of 1:1:1 was vacuum-filled into the pouch. The pouch was boiled at 98°C for 30 minutes. Test pieces measuring 15 mm x 300 mm were prepared from the pouches that had been subjected to the boiling treatment, and the laminate strength (N / 15 mm) between the NY and LLDPE was measured in the same manner as the initial adhesive strength.

[0108] (Adhesive strength: after retort) Using the packaging materials 12 to 14, pouches measuring 21 cm × 30 cm were prepared, and the contents were vacuum-filled with a sauce containing salad oil, ketchup, and 4.2% vinegar in a mass ratio of 1:1:1. The obtained pouches were retorted at 10 rpm, 120°C, 30 minutes, and a pressure of 3 MPa. Test pieces measuring 15 mm x 300 mm were prepared from the pouches that had been subjected to the above-mentioned retort treatment, and the laminate strength (N / 15 mm) between the NY and the CPP, or between the aluminum foil and the CPP, was measured in the same manner as for the initial adhesive strength.

[0109] (Releasability 1) For packaging materials 1 to 18, test pieces measuring 3.0 cm x 3.0 cm were cut out and immersed and stirred in 50 g of a 2% aqueous solution of sodium hydroxide at 70°C at a rotation speed of 100 rpm. However, for packaging material 9, the test piece was cut from the packaging material after boiling, and for packaging materials 12 to 14, the test piece was cut from the packaging material after retorting. The time it took for both substrates in contact with the release adhesive layer to peel off was measured and evaluated according to the following criteria. ○: Within 6 hours, both substrates in contact with the detachable adhesive layer are completely peeled off (good) △: Within 6 hours or more and less than 12 hours, the two substrates in contact with the detachable adhesive layer are completely peeled off (usable) ×: Even after 12 hours, the two substrates in contact with the removable adhesive layer do not peel off at all (unusable)

[0110] (removal rate 1) Test pieces measuring 3.0 cm x 3.0 cm were cut out for packaging materials 1 to 18. However, for packaging material 9, the test piece was cut out from the packaging material after boiling, and for packaging materials 12 to 14, the test piece was cut out from the packaging material after retorting. Each test piece was immersed and stirred in 50 g of a 2% aqueous solution of sodium hydroxide at 70°C for 12 hours at a rotation speed of 100 rpm, and the two substrates in contact with the release adhesive layer were peeled off, followed by rinsing with water and drying to obtain a recycled substrate for the second substrate. The presence or absence of an absorption peak of the adhesive was confirmed using FT-IR for a total of five locations, including the edge and center, on the surface of the obtained recycled substrate where the removable adhesive layer had been in contact, and the substrate was evaluated according to the following criteria: Substrates that did not peel off from each other within 12 hours were deemed unsatisfactory. ◎: No adhesive absorption peak at all five locations (removal rate is approximately 100%: very good) ○: Adhesive absorption peak was observed in only one of the five locations (removal rate was about 80%: good) △: Adhesive absorption peaks in 2 to 3 of the 5 locations (removal rate is about 40 to 60%: usable) ×: Adhesive absorption peaks in 4 or more of the 5 locations (removal rate is about 20%: not usable)

[0111] [Table 3]

[0112] [Table 4]

[0113] The abbreviations in Tables 3 and 4 are as follows: NaOH: Sodium hydroxide Ink 1: Rio Alpha R631 White, manufactured by Toyo Ink Co., Ltd. Ink 2: Toyo Ink Co., Ltd. CCST 62 White Ink 3: NEW MAX 63 White, manufactured by Toyo Ink Co., Ltd.

[0114] According to the results in Tables 3 and 4 above, the packaging material of the present invention, which has a configuration in which at least a first substrate, a printed layer, a polyurethane-based adhesive layer for detaching the second substrate, and a second substrate are laminated in this order from the outer layer side, and the polyurethane-based adhesive layer is provided in contact with the second substrate, not only has excellent initial adhesive strength and after boiling and retorting, but also has excellent detachment properties of the sealant substrate, which is the second substrate, and can enhance the recyclability of the sealant substrate. In particular, Examples 5, 8 to 11, and 15, in which the acid value after compounding of the adhesive was 20 mgKOH / g or more and the polyisocyanate component was a derivative derived from hexamethylene diisocyanate, showed good releasing properties and removal rates. Moreover, Example 8, which contained a polyester polyol having a number average molecular weight of less than 3,000, was superior to Example 5 in initial adhesive strength.

[0115] <Evaluation of packaging materials 19-31> The following evaluations were carried out using the obtained packaging materials 19 to 31. The results are shown in Table 6.

[0116] (Adhesion strength: initial) Using packaging materials 19 to 31, the lamination strength (N / 15 mm) between both substrates in contact with the polyurethane-based removable adhesive layer was measured in the same manner as in (initial adhesive strength) for packaging materials 1 to 18 described above. (Removal 2) For packaging materials 19 to 31, test pieces measuring 3.0 cm x 3.0 cm were cut out and immersed and stirred in 50 g of a 2% aqueous solution of sodium hydroxide (NaOH) at 70°C at a rotation speed of 50 rpm. The time it took for the OPP and CPP to peel off was measured and evaluated according to the following criteria. ◎: OPP and CPP completely peeled off within 20 minutes (very good) ○: OPP and CPP are completely peeled off within 20 minutes to 1 hour (good) △: OPP and CPP completely peel off within 1 to 12 hours (usable) ×: OPP and CPP are not completely peeled off within 12 hours (unusable)

[0117] (removal rate 2) For packaging materials 19 to 31, test pieces measuring 3.0 cm x 3.0 cm were cut out and immersed and stirred in 50 g of a 2% aqueous solution of sodium hydroxide (NaOH) at 70°C for 1 hour at a rotation speed of 50 rpm to peel the OPP from the CPP, followed by rinsing with water and drying to obtain recycled CPP films measuring 3.0 cm x 3.0 cm. The presence or absence of an absorption peak of the adhesive was confirmed using FT-IR for a total of five locations on the surface of the obtained recycled CPP film where the removable adhesive layer was in contact, namely, the four edges and the center, and the film was evaluated according to the following criteria. Those that did not peel the OPP from the CPP within 1 hour were deemed unevaluable. ◎: No adhesive absorption peak at all five locations (removal rate is approximately 100%: very good) ○: Adhesive absorption peak was observed in only one of the five locations (removal rate was about 80%: good) △: Adhesive absorption peaks in 2 to 3 of the 5 locations (removal rate is about 40 to 60%: usable) ×: Adhesive absorption peaks in 4 or more of the 5 locations (removal rate is about 20%: not usable)

[0118] [Table 6]

[0119] According to the results in Table 6 above, Examples 17 to 28, in which phosphoric acid or a phosphoric acid derivative was added, showed improved desorption performance compared to Example 16. Furthermore, Examples 23 to 28, in which fine particles having an average particle size of 1 to 10 μm were added in addition to phosphoric acid, showed improved desorption performance or removal rate compared to Examples 18 and 22.

[0120] <Evaluation of packaging materials 32 to 34> The following evaluations were carried out using the obtained packaging materials 32 to 34. The results are shown in Table 7.

[0121] (Adhesive strength: initial) Using the packaging materials 32 to 34, the same adhesive strength as that of the packaging materials 1 to 18 described above was applied to the PET / LDPE EXT The laminate strength (N / 15 mm) between the sheets was measured.

[0122] (Adhesive strength: after boiling) A pouch measuring 21 cm×30 cm was prepared using the packaging materials 32 to 34, and water was vacuum-filled as the content. The obtained pouch was subjected to a boiling heat treatment at 85° C. for 30 minutes. From the pouches that had been subjected to the boiling treatment, test pieces measuring 15 mm x 300 mm were made, and the same test was carried out on the PET / LDPE adhesive strength as for the initial adhesive strength. EXT The laminate strength (N / 15 mm) between the sheets was measured.

[0123] (Removal 3) Three test pieces measuring 2.0 cm x 2.0 cm were cut out from the pouch after the boiling treatment, and were immersed and stirred in 50 g of a 2% aqueous solution of sodium hydroxide (NaOH) at 70°C at a rotation speed of 100 rpm. The time it took for the PET and LDPEEXT to peel off was measured, and the peeling was evaluated according to the following criteria. ◎: Within 20 minutes, all PET and LDPEEXT peeled off (very good) ○: Peeling between PET and LDPEEXT occurred completely within 20 minutes to 1 hour (good) △: The PET and LDPEEXT completely peel off within 1 to 12 hours (usable) ×: No peeling between PET and LDPEEXT within 12 hours (unusable)

[0124] (removal rate 3) A test piece measuring 2.0 cm x 2.0 cm was cut out from the pouch after the boiling treatment, and immersed and stirred in 50 g of a 2% aqueous solution of sodium hydroxide (NaOH) at 70°C for 1 hour at a rotation speed of 100 rpm to peel the PET from the LDPEEXT. After that, the test piece was washed with water and dried to obtain a recycled PE film measuring 2.0 cm x 2.0 cm. The obtained recycled PE film was checked for the presence or absence of an absorption peak of the adhesive at a total of five locations, the four edges and the center, on the surface where the removable adhesive layer was in contact, using FT-IR, and was evaluated according to the following criteria. If the PET and LDPEEXT did not peel off within one hour, the film was deemed unsatisfactory. ◎: No adhesive absorption peak at all five locations (removal rate is approximately 100%: very good) ○: Adhesive absorption peak was observed in only one of the five locations (removal rate was about 80%: good) △: Adhesive absorption peaks in 2 to 3 of the 5 locations (removal rate is about 40 to 60%: usable) ×: Adhesive absorption peaks in 4 or more of the 5 locations (removal rate is about 20%: not usable)

[0125] [Table 7]

[0126] The abbreviations in Table 7 are as follows: NaOH: Sodium hydroxide Ink 4: Rio Alpha R39 indigo, manufactured by Toyo Ink Co., Ltd. Ink 5: Rio Alpha R631 White, manufactured by Toyo Ink Co., Ltd.

[0127] According to the results in Table 7 above, packaging materials 32 to 34, in which a second substrate was laminated by extrusion lamination, had a thinner removable adhesive layer than conventional dry lamination, but exhibited good alkali releasability and removal rate as well as excellent laminate strength.

Claims

1. A packaging material having a configuration in which at least a first substrate, a printed layer, a polyurethane-based adhesive layer for removing the second substrate, and a second substrate are laminated in this order from an outer layer side, the polyurethane adhesive layer is provided in contact with the second substrate, the polyurethane-based adhesive layer is a cured product of an adhesive containing a polyol component and a polyisocyanate component, and the acid value of the adhesive is 5 to 45 mgKOH / g; the polyol component includes a polyester polyol, and the polyester polyol has a number average molecular weight of 3,000 to 20,000; The polyisocyanate component includes at least one selected from the group consisting of aliphatic polyisocyanates and araliphatic polyisocyanates, The packaging material, wherein the second substrate comprises a polyolefin.

2. The packaging material of claim 1 , wherein the polyester polyol has urethane bonds.

3. 3. The packaging material according to claim 1, wherein the polyurethane-based adhesive layer further contains a phosphorus oxyacid or a derivative thereof in an amount of 0.01 to 5 mass % based on the mass of the polyurethane-based adhesive layer.

4. The packaging material according to any one of claims 1 to 3, wherein the polyurethane-based adhesive layer further contains fine particles having an average particle size of 1 to 10 µm.

5. The packaging material according to claim 4, wherein the content of the fine particles is 0.1 to 10% by mass based on the mass of the polyurethane-based adhesive layer.

6. The packaging material according to any one of claims 1 to 5, wherein the polyurethane-based adhesive layer has a thickness of 1 to 6 µm.

7. The packaging material according to any one of claims 1 to 6, wherein the second base material is a layer formed by extrusion lamination, and the polyurethane-based adhesive layer has a thickness of 0.01 to 1 µm.

8. A packaging container, at least a part of which is formed from the packaging material according to any one of claims 1 to 7.

Citation Information

Patent Citations

  • Ink composition having elimination performance and method for eliminating ink composition from print

    JP1999209677A

  • Article having releasable surface layer, releasable surface layer-forming material, method for releasing and removing surface layer from article, and article having removed surface layer therefrom

    JP2001131484A

  • Latent hydrophilic resin and composition containing the resin

    JP2001261746A

  • Adhesive and laminate using the same and used for package

    JP2005132902A

  • Bag container, recycling method, and lamination method

    JP2019081608A